REVIEW OF FIQH MUAMALAH ON THE SANCTION FOR CANCELING THE SALE OF CATTLE WITH A FEE - Herlina, Popi; Yustiloviani, Yustiloviani; Nabilah, Wardatun (Institut Agama Islam Negeri Batusangkar, 2024)
This study aims to answer about the form of implementation and sanctions for canceling the sale and purchase of cattle with a reward from the perspective of fiqh muamalah. With the type of field research and descriptive qualitative approach. This research was conducted by going directly to the field to observe the process of implementing the sale and purchase of cattle in Jorong Sitakuak, Nagari Guru n then in the interview the researcher asked several questions directly to the party who made the transaction of buying and selling cattle with a fee then invited the informant to answer objectively. This research in data collection uses the Snawball Sampling technique. The findings of this study are that the implementation of the contract in the sale and purchase of cattle with a fee in Jorong Sitakuak, Nagari Gurun is known that there is a contract that occurs between the seller (cow owner) and the buyer, namely by the way the parties agree on the selling price of the cow and determine when the cow is brought by the buyer. Sanctions or fines applied in the sale and purchase of cattle with a fee are if the one who cancels the sale and purchase is the seller (cattle owner) then the fee must be returned twice. However, if the buyer is the one who cancels the sale, then the payment is lost. The muamlah fiqh review of the implementation of the sale and purchase of cattle with a fee in Jorong Sitakuak Nagari Gurun is permissible because this is in accordance with the Fatwa of the National Sharia Council that sanctions can be in the form of a fine of a sum of money whose amount is determined on the basis of an agreement. Then this research contributes to the sanction of canceling the sale and purchase of cattle with a fee in the perspective of fiqh muamalah.